2005
DOI: 10.2737/ne-rp-726
|View full text |Cite
|
Sign up to set email alerts
|

Mapping host-species abundance of three major exotic forest pests

Abstract: Periodically over the last century, forests of the Eastern United States have been devastated by invasive pests. We used existing data to predict the geographical extent of future damage from beech bark disease (BBD), hemlock woolly adelgid (HWA), and gypsy moth. The distributions of host species of these alien pests were mapped in 1-km 2 cells by interpolating host basal area/ha from 93,611 forest-inventory plots in 37 states. The interpolated surfaces were adjusted for forest density (percent land cover) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 26 publications
(11 reference statements)
2
65
1
Order By: Relevance
“…This region is characterized by small and sparse forest patches of preferred hosts for gypsy moth (Morin et al, 2005). This is consistent with previous research that found gypsy moth with Allee effects have a critical patch size, below which a population cannot persist (Verken, Kramer, Tobin, & Drake, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…This region is characterized by small and sparse forest patches of preferred hosts for gypsy moth (Morin et al, 2005). This is consistent with previous research that found gypsy moth with Allee effects have a critical patch size, below which a population cannot persist (Verken, Kramer, Tobin, & Drake, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…Biological variables included (1) whether or not the site was within an area in which gypsy moth defoliation (as determined through aerial detection surveys; USDA Forest Service 2013a, b) occurred at least once during the 5 years prior to the study (2004)(2005)(2006)(2007)(2008), (2) the gypsy moth egg mass density prior to egg hatch in 2009, and (3) the basal area of the gypsy moth's preferred host tree species at each site, according to Morin et al (2005); preferred host tree species include those in the genera Quercus, Betula, Crataegus, Populus, Salix, and Tilia (Liebhold et al 1995). The average maximum and minimum monthly temperatures (March-June 2009) and monthly precipitation (March-June 2009) for each site were obtained from the PRISM Climate Group, Oregon State University (2011).…”
Section: Additional Site Characteristicsmentioning
confidence: 99%
“…Host abundance was measured as the basal area per hectare of host tree species that are preferred hosts . This raster GIS layer was developed by interpolating host basal area from [90,000 forest inventory plots (Kingsley 1985) and then adjusting for forest density by multiplying interpolated host basal area by percentage forest cover (Morin et al 2004). Seventy-nine tree species in eastern North America are considered to be preferred hosts, but oaks (Quercus spp.)…”
Section: Antisynchrony Modelmentioning
confidence: 99%
“…Host tree abundance was based upon a 1 km raster GIS layer developed by Morin et al (2004). Host abundance was measured as the basal area per hectare of host tree species that are preferred hosts .…”
Section: Antisynchrony Modelmentioning
confidence: 99%